7g+5+3g=-5+8g

Simple and best practice solution for 7g+5+3g=-5+8g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7g+5+3g=-5+8g equation:


7g+5+3g=-5+8g

We simplify the equation to the form, which is simple to understand
7g+5+3g=-5+8g

We move all terms containing g to the left and all other terms to the right.
+7g+3g-8g=-5-5

We simplify left and right side of the equation.
+2g=-10

We divide both sides of the equation by 2 to get g.
g=-5

See similar equations:

| 157-y=270 | | -9s-10=-10s | | 30-y=188 | | -4v=6-5v | | 4(x+3)=4(x+11) | | -1-7j=-6j+8 | | 5(10)+2-4=p | | 15x+4y=55 | | 7x(n+2.9)= | | -9-9d=7-7d | | 28b^2c^4+30bc=2bc(14bc^3+15) | | 3b=2+b | | 1-4x=16+5-8x-4 | | 4p-9=3p | | 6v*.69231=1.46t | | 2x+20=8+4y | | 6(24-b)=174 | | 28ab^2c^3+30=2ab(14bc^3+15) | | (7x+12)-4x=(4x+63)-4x | | 16x=x^2+28 | | 10(12+x)=240 | | 2x+9=12x | | -96=-8(b+7) | | y^2-2y+1-x=0 | | 85(7+m)=1955 | | X+y=186 | | -10=-7u+3(u-2) | | 10-3f=-4f | | -(1+n)=-5n+5(1+2n) | | x^2-2xy+3x-6y=0 | | (-3w)=-10-4w | | 3x-32=-7x+5 |

Equations solver categories